Gambaran Rencana bekerja, Self Efficacy dan Kesiapan Kerja Siswa Sekolah Menengah Kejuruan di Provinsi Kepulauan Riau - Dewi Mulyani (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2024)
Young workers is an issue in Indonesia's demographic bonus. The Riau Islands as an industrial area are faced with the problem of unemployment. Even though human capital is one of the keys to sustainable development. Various issues related to the high unemployment among vocational school graduates are discussed. This research aims to find out an overview of work plans, self-efficacy and work readiness in class XII vocational school students in the Riau Islands Province. Research method with a quantitative approach. The results obtained from 3185 respondents. The percentage of choices after graduation, 67% want to work and the others want to continuing their sudies, being enterpreneur or don’t have plan yet. It was found that 61% of student who want to work, did not know which company they would look for work at. A simple linear regression statistical test found that self-efficacy was related to work readiness. Thus, Special Job Fairs in Vocational Schools and other stakeholders need to pay attention to increasing self-efficacy which is expected to make students better prepared to enter the world of work